Clinical efficacy and mechanism-of-action of recombinant IFNα-2b, and IFNα-2b in combination with γ-D-glutamyl-L-tryptophan, in chronic polypous rhinosinusitis with comorbid bronchial asthma - E. V. Bezrukova; E. A. Varyushina; M. A. Aflitonov; S. A. Artyushkin; A. S. Simbirtsev (Медицинская иммунология)
Known methods of treating chronic polypous rhinosinusitis do not have a significant effect on the progressive nature of the disease. Recently, anticytokine therapy has been developed and introduced. However, the high cost of drugs and the complexity of their production make it necessary to search for other drugs with similar mechanisms of action. Such immunotropic drugs can be recombinant IFNα-2b and the γ-D-glutamyl-L-tryptophan. The aim of the study is to study the mechanism of action and evaluate the effectiveness of local application of IFNα-2b and γ-D-glutamyl-L-tryptophan in chronic polypous rhinosinusitis with concomitant bronchial asthma. Patients of the first group (31 people) were injected with IFNα-2b at a dose of 1 million units into the polypous tissue for five days. Patients of the second group (31 people) were injected with IFNα-2b at a dose of 1 million units and γ-D-glutamyl-L-tryptophan at a dose of 0.1 mg into the polypous tissue for five days. Patients were observed for a year. Before treatment and 1 month after treatment, a biopsy of polypous tissue was performed with analysis of morphological changes. Local administration of IFNα-2b and its combination with the γ-D-glutamyl-L-tryptophan into polypous tissue causes a decrease in the activity of T2 inflammation: decreased intercellular edema, tissue compaction, decreased the number of lymphocytes, eosinophils, plasma cells infiltrating the mucous membrane of polypous tissue. An analysis of the study results based on an assessment of the size of polyps showed that a month after therapy, the size of the polyps decreased, and when using IFNα-2b with γ-D-glutamyl-L-tryptophan, the size of the polyps decreased by approximately 70%, and the use only recombinant IFNα-2b by 40%. After 6 months, there was an increase in polyp tissue by 10-20% compared to the values after 1 month. After a year, the growth of polyps remained at the level of the values obtained after 6 months. The use of both IFNα-2b, and its combination with the γ-D-glutamyl-L-tryptophan, is a pathogenetically substantiated method of treating chronic polyposis rhinosinusitis, which allows its use as a conservative therapy for this disease.